2004
DOI: 10.22358/jafs/73945/2004
|View full text |Cite
|
Sign up to set email alerts
|

Is Na-butyrate a growth factor in the preruminant calf? Preliminary results

Abstract: Na-butyrate was studied as a candidate food additive in artifi cial milk replacer, which may potentially replace the use of feed antibiotics in the preruminant calf. The results of two experiments employing Na-butyrate are shown. Supplementation of milk replacer with Na-butyrate increased pancreatic exocrine secretion, probably due to stimulation of secretagogue gut regulatory peptides, which in turn resulted in better digestion effi ciency and enhanced animal's growth. The carcass weight was also increased. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…(2008) found that Na-butyrate supplementation of dairy calves diet significantly increased intestinal papillae width and length. Also, Guilloteau et al (2004, 2010) showed that Na-butyrate supplementation increased nutrient digestibility and total daily pancreatic secretions in young calves. The improved ADG and feed efficiency of calves fed Ca-butyrate supplemented starter in the post-weaning period of the current study may be attributed to an improvement of rumen and small intestine capacity absorption, as reported in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…(2008) found that Na-butyrate supplementation of dairy calves diet significantly increased intestinal papillae width and length. Also, Guilloteau et al (2004, 2010) showed that Na-butyrate supplementation increased nutrient digestibility and total daily pancreatic secretions in young calves. The improved ADG and feed efficiency of calves fed Ca-butyrate supplemented starter in the post-weaning period of the current study may be attributed to an improvement of rumen and small intestine capacity absorption, as reported in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a red kidney bean lectin treatment was shown to result in an increased capacity of pancreatic enzyme secretion in the suckling piglets due to an increase in CCK secretion (Evilevitch et al 2005). In calves fed milk replacer containing soya proteins, sodium butyrate, used as an additive in the diet, improved the GIT maturation and increased pancreatic enzyme secretion simultaneously with an elevation of blood levels of gastrin and mainly CCK (Guilloteau et al 2004). Moreover, it was shown that the diet component digestibility depends on pancreatic enzyme quantity present in the proximal duodenum (Guilloteau et al 1999; Guilloteau & Zabielski, 2005 b ).…”
Section: Applications – Future Challengesmentioning
confidence: 99%
“…It has been reported that sodium butyrate supplementation in milk replacer (MR) has a positive effect on small intestine development in calves (Guilloteau et al, ; Pietrzak et al, ). In addition, butyrate has been shown to positively affect calf performance and health via the stimulation of intestinal cell proliferation and growth (Guilloteau, Romé, Normand, Savary, & Zabielski, ; Guilloteau et al, ; Hill, Aldrich, Schlotterbeck, & Bateman, ). Our research group reported that intra‐ruminal administration of sodium butyrate stimulated GLP‐2 secretion, whereas acetate and propionate administration had no effect on plasma GLP‐2 concentration in sheep (Elsabagh, Inabu, Sugino, & Obitsu, ).…”
Section: Introductionmentioning
confidence: 99%